Integrating the STEM Approach into Discovery Learning to Improve Students' Scientific Literacy in Temperature and Heat - Arini Rosa Sinensis; Roja Septiani; Putra, Febrianto; Firdaus, Thoha (Universitas Muhammadiyah Makassar, 2026)
Scientific literacy is an essential skill in physics education, as students must understand scientific principles, interpret evidence, and apply knowledge to real-world issues. In Indonesia, however, scientific literacy among students remains a concern, evidenced by low PISA science scores and predominantly teacher-centered classroom practices. This study aimed to analyze the effect of integrating the STEM approach into the Discovery Learning model on eleventh-grade students’ scientific literacy in the topic of temperature and heat. A quasi-experimental method with a non-equivalent control group design was employed at MA Nurul A'la Jatimulyo II during the odd semester of the 2025/2026 academic year. The participants were 58 eleventh-grade science students. The experimental class (n = 29) learned through STEM-integrated Discovery Learning (DL-STEM), whereas the control class (n = 29) received conventional instruction. Scientific literacy was measured using a 25-item multiple-choice test developed from five indicators: explaining scientific phenomena, using scientific evidence, identifying scientific statements, understanding phenomena, and solving problems. Data were analyzed using descriptive statistics, assumption tests, the Mann–Whitney test for initial equivalence, an independent-samples t-test for posttest comparison, effect size r, and N-Gain analysis. The results indicated that both groups had comparable baseline abilities. Post-intervention, the experimental group significantly outperformed the control group, with mean scores of 64.69 versus 53.93 (p < 0.001), and demonstrated a moderate effect size (r = 0.47). Moreover, N-Gain analysis revealed improvements across all scientific literacy indicators in the experimental group, categorized as moderate and surpassing those of the control group. The novelty of this study lies in mapping STEM components onto the Discovery Learning syntax through a simple thermos engineering task in temperature-and-heat instruction. These findings indicate that DL-STEM can support students in connecting physics concepts, scientific evidence, and engineering design, thereby contributing to scientific literacy-oriented physics education.